Gateway to the Hanuman Garhi temple complex - Temples of India Project Team (Jio Institute, 2024)
This is a gateway to the Hanuman Garhi temple complex. Behind this complex, the remains of an old fortification wall were found. This gateway is a semi-open space adorned with smaller niches on its exterior and interior walls. This gateway was probably a later addition to the temple complex, built entirely of stone.